Energy input, output and economic analysis in organic production of mango (Mangifera indica) cv. Dashehari - RAM, R A; VERMA, A K (The Indian Journal of Agricultural Sciences, 2015)
Energy input and cost analysis of any crop production helps in cost effective management of inputs for improving productivity and profitability. Energy input, output and economic analysis was carried out for various components in mango (Mangifera indica L.) production system. Irrigation consumed the least energy (63 MJ) and diesel oil ranked first (3 040.74 MJ) in energy consumption. Maximum input energy was consumed (8 121.49 MJ) with application of 50 kg vermicompost + 250 g Azospirillum + PSB culture/tree + vermiwash spray compared to 6 232.24 MJ with application of 50 kg FYM/tree. Total production cost per hectare was maximum `Rupees 26 989 with 50 kg vermicompost + 250 g Azotobacter + PSB culture/tree and minimum (Rupees 19 349) with application of 50 kg FYM/tree. Maximum net return (Rupees 61 741/ha) was recorded with 50 kg vermicompost + 250 g Azospirillum + PSB culture/tree and benefit cost ratio (3.74) was with application of 50 kg vermicompost/tree. The total investment in term of energy was increased with 50 kg vermicompost + 250 g Azospirillum + PSB culture/tree over application of 50 kg FYM/ tree but production cost also decreased by 28.89% and net return was improved by 138.8% with application of 50 kg vermicompost + 250 g Azospirillum + PSB culture/tree.